Rough-interval-based multicriteria decision analysis for remediation of 1, 1-dichloroethane contaminated groundwater. (February 2017) - Ren, Lixia; He, Li; Lu, Hongwei; Li, Jing
Abstract: A rough-interval-based multicriteria decision analysis method (RI-MCDA) is developed for supporting the selection of remediation strategies for 1, 1-dichloroethane contaminated sites. The concept of ''rough interval'' is introduced in the design framework to represent dual-uncertain parameters. Three rough-interval scenarios generated through pair-wise combining the values under three confidence levels (i.e. 68.3%, 95.4% and 99.7%) and one deterministic scenario adopted crisp numbers for parameters are introduced into the framework. The proposed method is then applied to a contaminated site in the Pudong district of Shanghai, China. Fifty remediation alternatives under four duration options (i.e. 5, 10, 15, and 20 years) and ten criteria, including daily total pumping rate, total cost and rough-interval risk information in light of uncertainty parameter (e.g. slope factor), are taken into consideration to compare different alternatives through RI-MCDA. Results indicated that the most desirable remediation strategy lied in A25 for the 5-year, A10 for the 10-year, A15 for the 15-year, and A11 for the 20-year remediation. Compared to the traditional MCDA, the proposed RI-MCDA shows the uniqueness in addressing the interaction between dual intervals of highly uncertain parameters, as well as their joint impact on the decision results, which reduces the subjectivity as much as possible. Highlights: This study proposes a rough-interval-based multi-criteria decision analysis method. The slope factor is represented as rough interval during the health risk assessment. RI-MCDA is applied to a 1, 1-dichloroethane contaminated aquifer in Shanghai, China. RI-MCDA is helpful for dealing with the dual-uncertain information for remediation.